2001
DOI: 10.1002/asi.10029
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the use of text summaries, plain thumbnails, and enhanced thumbnails for Web search tasks

Abstract: We introduce a technique for creating novel, enhanced thumbnails of Web pages. These thumbnails combine the advantages of plain thumbnails and text summaries to provide consistent performance on a variety of tasks. We conducted a study in which participants used three different types of summaries (enhanced thumbnails, plain thumbnails, and text summaries) to search Web pages to find several different types of information. Participants took an average of 67, 86, and 95 seconds to find the answer with enhanced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 16 publications
1
46
1
Order By: Relevance
“…Researchers have also studied many differences between paper and electronic texts, particularly in the case of reading (e.g. [11], and how users scan search result lists [16] but document triage has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also studied many differences between paper and electronic texts, particularly in the case of reading (e.g. [11], and how users scan search result lists [16] but document triage has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of literatures on this study [18,19], by summing up the literature, we found there are some common conclusions:  An information trail for another clue superiority is relative, depending on the user's information goals;  For the navigation task in a complex network information environment, the accuracy of information clues disorder will lead to search costs rise.…”
Section: The Basic Theory Of Information Foragingmentioning
confidence: 75%
“…Woodruff pointed out problem in selecting the appropriate link from a large number of links in the information foraging process, if the number of pages the user visited prior to the landing page, to retrieve the cost representing the cost function N curve, the probability of error link f (f = 0.015, 0.030, ···, 0.150) cannot be ruled out, changes in the retrieval cost growth is a linear trend, after a critical point is reached growth shows an exponential trend [18]. Hogg and Huberman, shows a search cost curve, critical point method shows the search result development from linear trend into the exponential trend [20].…”
Section: The Basic Theory Of Information Foragingmentioning
confidence: 99%
“…Since then thumbnails have been exploited to support searching and revisiting in many other studies (Woodruff et al, 2001(Woodruff et al, , 2002Dziadosz and Chandrasekar, 2002;Teevan et al, 2009;Aula et al, 2010;Morgan and Wilson, 2010;Jiao et al, 2010;Loumakis et al, 2011;Badesh and Blustein, 2012). Browsers also use thumbnails in a limited fashion to support revisiting.…”
Section: Methods For Presenting a Web Historymentioning
confidence: 99%